Project management workbook and PMP - Kerzner, Harold; Saladis, Frank P. (John Wiley and Sons, Inc. : Wiley, 2017)
"The purpose of this workbook is to provide ... meaningful exercises and homework problems that will enhance the knowledge of the subjects included in the textbook Project management: a systems approach to planning, scheduling, and controlling (12th edition) by Harold Kerzner, Ph.D"--Page xi.